Factors affecting willingness to adopt climate insurance among smallholder farmers in Sri Lanka - Aheeyar, Mohamed M. M.; Amarasinghe, Upali; Amarnath, Giriraj; Alahacoon, Niranga (Elsevier, 2023)
Drought is an almost annual phenomenon affecting many parts of Sri Lanka, causing huge damage to agriculture and losses to the broader economy in general and farmers in particular. Climate change threatens to exacerbate these risks. Risk transfer mechanisms, such as crop insurance schemes, may help buffer farmers against these hazards and has gained attention as an adaptation response to become an important element in agricultural risk management. Despite the numerous efforts over several decades to popularize crop insurance as a risk transfer tool in the country under heavy subsidies, farmers' voluntary enrollment in crop insurance has been very low. Therefore, understanding the farmers' behaviors and attitudes towards crop insurance and the potential of such programs in emerging climate-induced vulnerabilities is critical to enhancing the welfare of the farming community. This paper assesses the factors that influence willingness to enroll for crop insurance among farmers in irrigated and rainfed farming system in the drought-prone North Central Province of Sri Lanka using a logistic regression model. The study sample consisted of 149 irrigated farmers and 51 rainfed farmers selected randomly. Regression results show that farmer’s age, agriculture as the primary source of income, irrigation as the source of water, and availability of supplementary water source are significantly related to willingness to pay (WTP) for insurance. The overall results indicate the role of household socioeconomic factors and their contextualized risk perceptions shape the adoption decision of crop insurance. The findings of the paper contribute to that end through primary data from a rainfed and irrigated areas in the province. Although the present research was carried out in a limited area, the study area is dominated by the traditional nature of agricultural practices by smallholder farmers in a drought exposed environment, the findings of the study should apply to the rest of the dry zone areas in the country. The results on factors affecting farmers' willingness to purchase crop insurance assist the practitioners and policymakers to draft the guidelines and strategies for more inclusive interventions for agriculture risk management and building farmer resilience.